PENERAPAN PENCABUTAN HAK POLITIK TERHADAP PELAKU TINDAK PIDANA KORUPSI DI INDONESIA - Gabriel, Alexander Ricardo; Erdianto, Erdianto; Rahmadan, Davit (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The growing criminal acts of corruption have made it hard work for law enforcement in Indonesia. In terms of actors, corruption is carried out not by ordinary people, but by those who have an agreed position and status in society. The phenomenon of the rise of public officials and political figures who have been trapped in corruption cases has developed enough. One effort to provide a deterrent effect for those who commit acts of corruption is to provide freedom in the form of revoking political rights.This type of research can be classified in normative legal research, namely legal research conducted by researching library materials. This study examines the subject matter in accordance with the scope and identification of the problem through a statute approach carried out by examining the laws and regulations that relate to the legal issue under study. In this study the authors conducted a study of the principles of law by utilizing descriptive methods. Data collection techniques used in the Normative Legal Research are library research methods (library research) which uses the library as a means of collecting data, by studying books as reference material related to the problems to be studied.The conclusion that can be obtained from the results of the study is the application of revocation of political rights to perpetrators of corruption in Indonesia still raises the pros and cons. The effectiveness of the adoption of political rights against perpetrators of corruption against corruption perception in Indonesia is still not good. The perception indicators of corruption that are still lagging behind a number of countries in ASEAN have an effect on the level of Indonesian competitiveness in the eyes of investors, because the corruption index is still low compared to neighboring countries. corruptors are still involved in the political process. The ideal concept of setting the revocation of political rights to perpetrators of corruption in the future must pay attention to the time limit for its imposition related to the crime committed by the convicted person also associated with the value of the loss.Keywords: Revocation of Political Rights, Actors, Crime, Corruption